Canadian women's attitudes toward noninvasive prenatal testing of fetal DNA in maternal plasma*. (16th December 2016) - Pariente, Gali; Hasan, Lara; Gadot, Yifat; De Souza, Leanne R.; Lebovic, Gerald; Berger, Howard
Abstract: Objective : To determine the perceptions and attitudes of Canadian women to Noninvasive Prenatal Testing of fetal DNA. Study design : A designed questionnaire was administered to women attending the outpatient antenatal clinic at a tertiary urban hospital. Attitudes to current and new prenatal screening modalities were assessed using a five-point Likert scale. Bowker's test of symmetry was used to compare individual responses regarding the two screening modalities. Changes in women's responses pre- and post-delivery were also compared. Results : One hundred and twenty-nine women were enrolled in this study. 88% of women state that they would perform prenatal screening via fetal DNA in the maternal plasma if available. When compared to conventional screening, significantly less women believe that the NIPT should be available upon request for non-medical traits (36.4% versus 60.4%, p < 0.001). When compared to their answer before delivery, more women agreed that screening with fetal DNA in maternal plasma could be used in a negative way to select for desired non-medical traits such as gender. Conclusions : The use of fetal DNA in the maternal plasma is widely accepted in our Canadian population as a future method of noninvasive prenatal screening despite recognition of certain ethical concerns. This information can be used when implementing new genetic screening programs.